2019
DOI: 10.1111/opo.12628
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of Spot and Plusoptix photoscreeners in detecting amblyogenic risk factors in children: a systemic review and meta‐analysis

Abstract: Purpose Amblyopia is a permanent visual impairment developed in early childhood. Recently, instrument‐based photoscreeners have been widely used for vision screening to detect amblyopia risk factors, which is key for the prevention and treatment of amblyopia. This meta‐analysis aims to evaluate the diagnostic test accuracy of Spot and Plusoptix photoscreeners in detecting risk factors for amblyopia in children. Methods An electronic literature search was performed in October 2018 using the MEDLINE, Embase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The Spot photoscreener we used in this study has been shown to have good consistency with cycloplegic refraction test in our previous study [ 5 , 31 , 32 ]. It is also reported to have an overall high sensitivity (91.7%) and specificity (82.6%) in detecting amblyogenic risk factors in children [ 10 ], suggesting its good test accuracy. This evidence proved it a reliable screener for myopia.…”
Section: Photoscreening and Corrections For Photoscreener Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Spot photoscreener we used in this study has been shown to have good consistency with cycloplegic refraction test in our previous study [ 5 , 31 , 32 ]. It is also reported to have an overall high sensitivity (91.7%) and specificity (82.6%) in detecting amblyogenic risk factors in children [ 10 ], suggesting its good test accuracy. This evidence proved it a reliable screener for myopia.…”
Section: Photoscreening and Corrections For Photoscreener Resultsmentioning
confidence: 99%
“…This increased myopic measurement could be explained by the pupil dilation or the accommodation induced by the 1 m working distance of screener [ 5 ]. It is also the reason of the relatively high referral rate for amblyopia risk factors from the photoscreeners [ 10 , 11 ].…”
Section: Photoscreening and Corrections For Photoscreener Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Patients with PACG, to some extent, have specific anatomic abnormalities, characterized by the thick lens and short axial length of eyeball which may cause the pupillary block, narrowed anterior chamber and subsequent intraocular pressure (IOP) increase. [3,4] Based on the pathogenesis, removing the thick lens seems to be necessary to treat PACG.…”
Section: Introductionmentioning
confidence: 99%
“…These results are also contradicting to a study performed under 7 years at a different geographical location. 33 The refractive cut-off values used here were as per the AAPOS guidelines. 27 A modification in the referral criteria (for myopia, hypermetropia, and astigmatism) could improve the sensitivity and specificity values.…”
Section: Discussionmentioning
confidence: 99%